2018
DOI: 10.1039/c8cp00626a
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance perturbation on Schiff base–counterion interactions by His30 and the extracellular Na+-binding site in Krokinobacter rhodopsin 2

Abstract: Proton pumping ability of a light-driven Na+ pumping Krokinobacter rhodopsin 2 (KR2) is inhibited by H30A and lack of bound Na+ at extracellular site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…It means that the rearrangements on the surface of the KR2 occur not directly in response to the retinal isomerization upon photon absorption, but rather due to the redistribution of charges in the central inner part of the protein protomer. Such long-distance interactions between the RSB-counterion and pentamer surface were already studied for the WT and H30A variant of KR2 14,25 . Recently, it was also shown that there is an allosteric communication between the interprotomer Na + -binding site and the RSB hydrogen bond already in the ground state 26 .…”
Section: Resultsmentioning
confidence: 97%
“…It means that the rearrangements on the surface of the KR2 occur not directly in response to the retinal isomerization upon photon absorption, but rather due to the redistribution of charges in the central inner part of the protein protomer. Such long-distance interactions between the RSB-counterion and pentamer surface were already studied for the WT and H30A variant of KR2 14,25 . Recently, it was also shown that there is an allosteric communication between the interprotomer Na + -binding site and the RSB hydrogen bond already in the ground state 26 .…”
Section: Resultsmentioning
confidence: 97%
“…As structure of KR2 depends dramatically on the oligomeric state, we decided to mutate the oligomerization interface to destroy the pentameric assembly and simultaneously check the functional activity of the protein variants. Recently, it was shown that the alterations at the oligomerization interface around His 30 affect the oligomeric assembly and change protein selectivity and Schiff base–counterion interaction ( 8 , 20 , 28 ). Consequently, we generated H30L, H30K, and Y154F mutants of KR2, which were aimed at breaking the His 30 -Tyr 154 hydrogen bond, located in the middle of the oligomerization interface and therefore stabilizing the pentamer.…”
Section: Resultsmentioning
confidence: 99%
“…There is also no clear effect on the 15 N resonance of the protonated Schiff base (not shown). An additional shielding was only reported for KR2 H30A (Shigeta et al, 2018). Furthermore, no chemical shift changes could be detected for T83 (data not shown), which is directly involved in coordinating Na + binding (Fig.…”
Section: Effect Of Na +mentioning
confidence: 87%